Dataset: Thermokarst disturbance drives concentration and composition of metals and polycyclic aromatic compounds in lakes of the western Canadian Arctic - Thienpont, Joshua; Eickmeyer, David; Kimpe, Linda; Blais, Jules (2020)
Natural Sciences and Engineering Research Council of Canada